Pilot Cluster Randomized Controlled Trial of Integrative Nutritional Counseling Versus Standard Diabetes Self-Management Education for Chinese Americans with Type 2 Diabetes (Mary Ann Liebert, 2020)
Purpose: Chinese Americans (CAs) with diabetes and limited English proficiency often struggle to adhere to standard diabetes diets focused on food measurement/restriction. Chinese medicine principles commonly inform food choices among CAs but are rarely acknowledged in nutritional interventions. We developed and tested feasibility of a theoretically informed integrative nutritional counseling (INC) program that combines Chinese medicine principles with biomedical nutrition standards. Methods: We randomized diabetes self-management education (DSME) classes to include either: (1) usual nutrition curriculum based on American Diabetes Association (ADA) recommendations delivered by a diabetes educator (control) or (2) INC curriculum based on a combination of ADA recommendations and Chinese medicine principles delivered by a diabetes educator and a licensed acupuncturist (intervention). All DSME enrollees were invited to participate in research entailing data collection at three time points: baseline, after the DSME nutrition class, and at 6-month follow-up. Using validated measures, we collected dietary self-efficacy, diabetes distress, diet satisfaction, and dietary adherence. We also measured weight and glycemic control. Results: Study participants were 18 Cantonese-speaking patients with diabetes who were predominantly female and older, with low levels of income and acculturation. Intervention and control groups were similar at baseline. INC performed similarly to usual DSME with 100% of participants reporting the INC booklet helped their learning. Dietary adherence significantly improved in participants who received the INC curriculum. Conclusion: INC is feasible to implement as part of DSME classes and shows promise as a complementary culturally sensitive addition to usual diabetes nutrition education for CA patients.